Comparision of Gingival and Umbilical Cord Stem Cells Based on Its Modulus and Neuronal Differentiation. Issue 8 (25th April 2017) - Subbarayan, Rajasekaran; Murugan Girija, Dinesh; Mukherjee, Joynarayan; Mamidanna, Sri Ramachandra Rao; Ranga Rao, Suresh
ABSTRACT: The availability of Human Umbilical Cord‐derived Mesenchymal Stem Cells (HUCMSCs) from a single sex being a major limitation for the utilization of a potential stem cell, it is highly desirable to utilize, an autogenous pluripotent cell with desirable biological and mechanical properties in clinical situations. Comparison of Human Gingival Mesenchymal Stem Cells (HGMSCs) with HUCMSCs demonstrates; MSCs derived from gingiva have higher proliferation rate and higher population doubling time than Umbilical Cord. Unlike HUCMSCs, immunofluorescence studies showed the presence of pluripotency markers OCT‐4 and NANOG predominantly in the cytoplasm of HGMSCs which was confirmed by Western blot. The mechanical property, such as modulus of elasticity of HGMSCs, is on par with HUCMSCs, but the surface roughness found to be lesser in HGMSCs, which may suggest HGMSCs greater adhesive property to the extracellular matrix. There is a marginal difference in the neuronal differentiation rate between HGMSCs and HUCMSCs; both the cells expressed positivity for several neuronal lineage markers. Hence, HGMSCs represent an autogenous source of mesenchymal stem cells, which are easy to procure with least morbidity, multipotent in nature with desirable biological, and mechanical properties, probably an ideal candidate for clinical applications. J. Cell. Biochem. 118: 2000–2008, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Comparison of human gingival and human umbilical cord stem cells based on biological and mechanical properties.